Trade Matters : New Opportunities for the Caribbean - World Bank (Washington, DC, 2015)
Trade is essential for Caribbean countries development and poverty reduction. Given their small market size, they are dependent on exports to produce manufactured products at efficient scale. And given their natural amenities, they rely on tourism as a major spur to economic activity. Trade in the Caribbean thus makes an essential contribution to increasing employment and reducing poverty by supporting growth. At the same time, the high dependence on trade also makes Caribbean economies vulnerable to external shocks. For example, the global financial crisis imposed substantial job losses in sectors such as tourism that the poor rely on for employment. This report employs several different, but complementary, empirical approaches to analyzing the impact of this emerging new trade environment on shared prosperity in the Caribbean. These include the following six topics, with each corresponding to an individual chapter: (i) assessment of the Caribbean s performance in reaping the opportunities offered by the new trade environment; (ii) identification of the main determinants of Caribbean countries trade performance; (iii) discussion of the role of innovation and access to keys services in improving the productivity of exporting firms; (iv) exploration of how regional integration and other trade agreements could boost Caribbean trade performance; (v) firm-level examination of the implications of trade for employment; and (vi) identification of which households are involved in international trade and the implications of trade for their socio-economic status.